THE INFLUENCE OF INSTAGRAM SOCIAL MEDIA USE IN KAMPUNG KANDAGA COMMUNITY - Nur Hariandi; Paulus Subandi; Rustiadi Heri Purnomo (SEAN Institute, 2021)
Social media is a term that describes a variety of technologies that are used to bind people into collaboration, exchange information, and interact through web-based message content. Path occupies the fourth position with the dominance of users ranging in age from 20 to 25 years.We will conduct research in the form of a survey. The survey is a quantitative basic form